IMAGING DIAGNOSIS—COMPUTED TOMOGRAPHIC, SURGICAL, AND HISTOPATHOLOGIC CHARACTERISTICS OF AN INFILTRATIVE ANGIOLIPOMA IN A DOG. Issue 3 (22nd May 2014) - Kraun, Michael B.; Nelson, Nathan C.; Hollinger, Charlotte
<x xml:space="preserve">Abstract</x> A 6‐year‐old female spayed Shetland Sheepdog presented for evaluation of a subcutaneous mass over the right prescapular region. The mass had been cytologically diagnosed as a lipoma by the referring veterinarian 20 months prior, but had grown significantly and was very firm. CT scan of the mass was suggestive of neoplasia; however, the tissue of origin could not be determined. Histopathologic evaluation diagnosed infiltrative angiolipoma, and marginal resection of the tumor was performed. Infiltrative angiolipomas are benign but locally aggressive neoplasms uncommonly reported in veterinary medicine. This report correlates the clinical, CT, and histopathologic characteristics of an infiltrative angiolipoma.